2022
DOI: 10.1109/access.2022.3172301
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Typhoon Track and Intensity Using a Generative Adversarial Network With Observational and Meteorological Data

Abstract: To save lives and reduce damage from the destructive impacts of a typhoon, an accurate and fast forecast method is highly demanded. Particularly, predictions for short lead times, known as nowcasting, rely on fast forecasts allowing immediate emergency plannings in the affected areas. In this paper, we propose a generative adversarial network that operates on a single graphics processing unit, to predict both the track and intensity of typhoons for short lead times within fractions of a second. To investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…GANs and diffusion models are not limited to producing images and have many potential applications in other fields, including meteorology and climate science. Such applications include downscaling climate model output (Cheng et al ., 2021), ensemble weather prediction (Bihlo, 2021), nowcasting (Rüttgers et al ., 2022) and even storm surge models (Lütjens et al ., 2020). Generative models can also now produce convincing text output.…”
Section: Discussionmentioning
confidence: 99%
“…GANs and diffusion models are not limited to producing images and have many potential applications in other fields, including meteorology and climate science. Such applications include downscaling climate model output (Cheng et al ., 2021), ensemble weather prediction (Bihlo, 2021), nowcasting (Rüttgers et al ., 2022) and even storm surge models (Lütjens et al ., 2020). Generative models can also now produce convincing text output.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ref. [111] designed a GAN based approach to predict both the track and intensity of typhoons for short lead times within fractions of a second. The experimental results indicated that learning velocity, temperature, pressure, and humidity along with satellite images have positive effects on trajectory prediction accuracy.…”
Section: Gan-based Tracking Methodsmentioning
confidence: 99%
“…In addition, Figure 4 shows a comparison of algorithm structure between two categories. [110] 2021 GAN with deep multi-scale frame prediction method [111] 2022 GAN to predict both the track and intensity of typhoons RNN-based [112] 2017 A convolutional sequence-to-sequence autoencoder [113] 2018 MNNs for typhoon tracking [114] 2018 A CLSTM based model [115] 2021 A CLSTM layer with FCLs [116] 2022 A CLSTM with 3D CNN based on multimodal data [117] 2022 An echo state network-based tracking Fire Traditional [118] 2017 Identify possible fire hotspots from two bands of AHI [119] 2018 A threshold algorithm with visual interpretation [120] 2019 A multi-temporal method of temperature estimation [121] 2020 Temperature dynamics by data assimilation [122] 2022 Wildfire tracking via visible and infrared image series DL-based [123] 2019 3D CNN to capture spatial and spectral patterns [124] 2019 Inception-v3 model with transfer learning [125] 2021 Near-real-time fire smoking prediction [126] 2022 Combine the residual convolution and separable convolution to detect fire [127] 2022 Multiple Kernel learning for various size fire detections…”
Section: Ship Trackingmentioning
confidence: 99%
“…Recently, neural networks have shown promising results in addressing atmospheric flow problems, such as typhoon prediction [5,6]. Neural-networkbased wind predictions have also been investigated by various researchers [7,8,9].…”
Section: Introductionmentioning
confidence: 99%